Vestibular contributions to a right-hemisphere network for bodily awareness: Combining galvanic vestibular stimulation and the "Rubber Hand Illusion". (March 2015) - Ferrè, Elisa Raffaella; Berlot, Eva; Haggard, Patrick
Abstract: An altered sense of one's own body is a common consequence of vestibular damage, and also of damage to vestibular networks in the right hemisphere. However, few experimental studies have investigated whether vestibular signals contribute to bodily awareness. We addressed this issue by combining an established experimental model of bodily awareness (Rubber Hand Illusion -RHI) with galvanic vestibular stimulation (GVS) in healthy participants. Brief left anodal and right cathodal GVS (which predominantly activates vestibular networks in the right hemisphere), or right anodal and left cathodal GVS, or sham stimulation were delivered at random, while participants experienced either synchronous or asynchronous visuo-tactile stimulation of a rubber hand and their own hand. The drift in the perceived position of the participant's hand towards the rubber hand was used as a proxy measure of the resulting multisensory illusion of body ownership. GVS induced strong polarity-dependent effects on this measure of RHI: left anodal and right cathodal GVS produced significantly lower proprioceptive drift than right anodal and left cathodal GVS. We suggest that vestibular inputs influence the multisensory weighting functions that underlie bodily awareness: the right hemisphere vestibular projections activated by the left anodal and right cathodal GVS increased the weight of intrinsic proprioceptive signals about hand position, and decreased the weight of visual information responsible for visual capture during the RHI. Highlights: Left-anodal galvanic vestibular stimulation decreases the strength of RHI. Vestibular system influences multisensory processes underlying bodily awareness. Right hemisphere vestibular projections modulate bodily awareness.